Understanding the effect of market orientation on circular economy practices: The mediating role of closed-loop orientation in German SMEs - Corinna Vera Hedwig Schmidt; Bastian Kindermann; Cassian Felix Behlau; Tessa Christina Flatten (Business Strategy and the Environment, 2021)
The implementation of circular economy (CE) practices is considered a key driver towards sustainable development of firms. Earlier studies point to the general strategic approach of market orientation as an antecedent to CE practice implementation. Still, insights are limited as the mechanisms underlying this relationship remain unclear. Based on a sample of 121 German small and medium-sized enterprises (SME), we empirically examine how the strategic approach of closed-loop orientation mediates the relationship between market orientation and the implementation of three types of CE practices. Using structural equation modelling, we find that while market orientation is positively related to all three types of CE practices, closed-loop orientation mediates these relationships for only two. Our study extends CE literature by suggesting that market orientation is translated into closed-loop orientation to spur CE practice implementation. We also offer a differentiated understanding of CE practice implementation in the context of German SMEs.
Keywords: 330; circular economy practices; closed-loop orientation; market orientation; natural-resource-based view; small and medium-sized enterprises; sustainable development